A framework for uniting space and time in the mind and brain - Houser, Troy M. (Frontiers in Cognition, 2025)
Kant argued that all experience is perceived through the lens of a priori concepts of space and time. That is, Kantian philosophy supposes that knowledge is formatted in terms of space and time. This article argues that space can be reduced to time and thus that the only a priori concept used to format knowledge is time. To build this framework, the article focuses on how humans discount time when making intertemporal choices. Celebrated temporal discounting models, such as the exponential and hyperbolic discounting models, are reviewed before arguing in favor of a more ecologically motivated account that suggests that hyperbolic discounting emerges from exponential discounting and uncertainty. The ecological account of temporal discounting is then applied to spatial navigation. Along the way, findings from neurobiology and principles from computational mechanisms are used to substantiate claims. Reducing space to time has important implications in cognitive science and philosophy and can inform a suite of seemingly distinct literatures.